Structural basis for the inhibition of translation through eIF2α phosphorylation - Yuliya Gordiyenko (Nature Portfolio, 2019)
During stress, protein synthesis is inhibited through phosphorylation of the initiation factor eIF2 on its alpha subunit and its interaction with eIF2B. Here the authors describe a structure of the yeast eIF2B in complex with its substrate - the GDP-bound phosphorylated eIF2, providing insights into how phosphorylation results in a tighter interaction with eIF2B.